A STUDY ON TEACHING STRATEGIES APPLIED BY ENGLISH TEACHER IN TEACHING SPEAKING SKILLS AT EIGHTH GRADE STUDENTS OF SMP NEGERI 1 TOMA - Astika Mega Duha (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
Teaching strategies applied by English teachers to teach speaking skills are important to enhance the student's speaking skills. Teaching strategies applied by English teacher can help the students to understand English skills: listening, reading, writing, and speaking. Therefore, the teacher needs to apply teaching strategies appropriately in the classroom. This research aimed at finding teaching strategies applied by English teachers in teaching speaking skills in the eighth grade of SMP Negeri 1 Toma. The researcher used a qualitative method with a descriptive approach. The data used by the researcher is primary data because this data is collected through observation and interviews. The results showed that English teachers applied four teaching strategies in teaching speaking skills these strategies are question-answers strategies, group discussion strategies, project strategies, and role play or simulation teaching strategies. It can be concluded that teaching strategies in teaching speaking skills are very good to be applied in teaching speaking skills for students because they can help teachers improve the speaking skills of students. The researcher hopes the English teacher will be expanding and developing teaching strategies applied teaching speaking skills.